The role of civil society institutions for the city of Mila in the face of emergency crises The health crisis (Corona pandemic) as a model - فنور, بسمة (Milev Journal of Research and Studies, 2023)
Through this study, we will try to research the role played by the civil society associations of Mila during the health crisis caused by the third wave of the Corona pandemic. Algeria - like the whole world - has recently suffered from the effects of the health crisis left by the Covid pandemic, where the citizen suddenly found himself facing the repercussions of this crisis, from a shortage of medicines and a shortage of oxygen, in front of the state's inability to face these repercussions and control the market for these materials and organize their distribution, This contributed to reshaping the prevailing ideas about relying entirely on the state, and the rate of participation and volunteering in civil society associations increased to face the repercussions of this crisis. Civil society institutions today have become one of the most important social structures that contribute to the advancement of society and its advancement, by involving the citizen in finding solutions to his daily problems, and expressing his opinion on the crucial issues of the nation, which works to develop awareness of citizenship and increase the sense of belonging, which constitutes an impenetrable fortress in Facing crises that may be exposed to society.